ENSIKLOPEDIA TOKOH-TOKOH PEJUANG LAMPUNG BERMUATAN NILAI-NILAI KARAKTER BERBASIS ANDROID - Heru Apri Saputra; Kuswono Kuswono (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
This study aims to develop an encyclopedia of Lampung warrior figures and describe theirfeasibility. The feasibility test was carried out at Metro 6 Public High School. The study uses aresearch and development (R&D) method adapted from the Sugiyono Level 1 model (produces adesign but does not test). Stages of research that is analyzing the potential or problem, gatheringinformation through observation, in-depth interviews, document collection, product design, media validation, media improvement, and completion of the encyclopedia product Lampung herofigures.The results of the study are the learning media encyclopedia of Lampung warrior figures designedin accordance with the 2013 curriculum and BC curriculum in the subject of the 20th centuryIndonesian resistance strategy. The results of media validation for phase 1 were 76% (Eligible) forstage 2 by 93% (Very Eligible), the results obtained from media validation between stage 1 andstage 2 experienced an increase of 17%. Then in the results of the validation of stage 1 material by80% (Eligible), stage 2 by 90% (Very Eligible), between stage 1 and stage 2 has increased by 10%.And the results of student responses by 90% (Very Eligible). From the results of the validation itcan be concluded that the encyclopedia media figures of Lampung warrior deserve to be tested.